1999
DOI: 10.1046/j.1469-8137.1999.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and allocation of resources in two waterlogging‐tolerant grasses

Abstract: This study focuses on the following questions : (i) whether reductions in root :shoot ratio have a cost in terms of nutrient balance of the plant, and (ii) whether changes in resource-allocation patterns are proportional among different resources. Our approach was to analyse the variations in the allocation pattern induced by soil waterlogging. A pot experiment was conducted to analyse the effects of waterlogging on biomass, phosphorus (P) and nitrogen (N) accumulation of Paspalum dilatatum and Danthoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
3
34
1
1
Order By: Relevance
“…This hypothesis predicts that regrowth following defoliation will be larger for plants that accumulated P during a previous period. We performed two experiments with four grass species which are dominant and co-dominant in the Flooding Pampa grasslands, an area where P luxury consumption is a common response, both at functional group and individual level (Ginzo et al 1982;Rubio and Lavado 1999;Semmartin et al 2007). The Wrst experiment, aimed at generating P luxury consumption by fertilization, resulted in one species (Sporobolus indicus) showing luxury consumption.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis predicts that regrowth following defoliation will be larger for plants that accumulated P during a previous period. We performed two experiments with four grass species which are dominant and co-dominant in the Flooding Pampa grasslands, an area where P luxury consumption is a common response, both at functional group and individual level (Ginzo et al 1982;Rubio and Lavado 1999;Semmartin et al 2007). The Wrst experiment, aimed at generating P luxury consumption by fertilization, resulted in one species (Sporobolus indicus) showing luxury consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mattos et al (2005) reported that flooding caused a lower LMR in Brachiaria spp. As suggested by Rubio & Lavado (1999), the reduced allocation to roots in flooded plants could be a strategy to decrease the higher maintenance respiration of roots, when compared to that of shoots. Also, because roots cannot satisfy their own oxygen requirements, a smaller root system could be more easily ventilated by the shoot under waterlogging conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Rubio & Lavado (1999) Brachiaria spp. Also, a higher proportion of biomass allocated to leaves was observed in flooded Leontodon taraxacoides (Asteraceae) by Grimoldi et al (1999).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have found that waterlogging may affect plant growth compared to drained conditions or according to different levels of flooding (Waldren et al 1987(Waldren et al , 1988Mendoza et al 2005). Longer durations of waterlogging have been shown to inhibit leaf area expansion (Dale and Causton 1992;Lenssern et al 2002) and reduce biomass allocation to below-ground resources (Rubio and Lavado 1999). It was correlated with some chemical change in waterlogging condition, such as redox potential of the soil, exchangeable ferric iron and manganese considerably decreasing (Etherington 1984;Waldren et al 1987Waldren et al , 1988.…”
Section: Discussionmentioning
confidence: 99%